Don't Fall in the (Generation) Gap!-A Workshop Addressing Generational Differences in Medical Training - Susan Martinelli; Candra Bass; Todd Zakrajsek; David Mayer (Association of American Medical Colleges, 2015)
Abstract Faculty working in medical teaching programs are increasingly frustrated that their learners appear to have different priorities and values than they themselves had when they were in training. Residents demonstrate frustration with faculty expectations regarding work duties and interaction with patients and other medical professionals. Many of these perceptions are viewed as personal complaints or conflicts with the individuals involved. In actuality, a significant component of these issues may be due to generational differences between educators and learners. This 90-minute workshop is meant to introduce and discuss generational differences, show how these differences might play out in a graduate medical education environment, and demonstrate ways to increase professionalism through a better understanding of these differences. Although this workshop has been conducted with anesthesia and surgery faculty and residents, it can easily be adapted to a wide variety of clinical departments and training programs. To the best of our knowledge, no similar form of generational training at the graduate medical education level has been published. This workshop has been presented in a number of forums differing in size and group composition: for instance, a group of 40 faculty and residents in our department, a group of 10 interns in our department, and a group of 20 faculty at a national meeting. A consistent theme in the wrap-up period and in workshop evaluations was that exposure to this content enhanced the ability of participants (both teachers and learners) to be open-minded and realize that these differences are real and do affect our educational environment. Overall, this workshop is easy to facilitate and has been well received. It appears to function well as an introduction to generational differences in the resident training environment for both learners and educators. Participants noted that the workshop provided a nonthreatening environment to discuss potentially sensitive issues.